2001
DOI: 10.1128/jvi.75.12.5498-5503.2001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of L-Deleted Foot-and-Mouth Disease Virus Replication by Alpha/Beta Interferon Involves Double-Stranded RNA-Dependent Protein Kinase

Abstract: We previously demonstrated that the ability of foot-and-mouth disease virus (FMDV) to form plaques in cell culture is associated with the suppression of alpha/beta interferon (IFN-␣/␤). In the present study, we used Escherichia coli-expressed porcine and bovine IFN-␣ or -␤ individually to demonstrate that each was equally effective in inhibiting FMDV replication. The block in FMDV replication appeared to be at the level of protein translation, suggesting a role for double-stranded RNA-dependent protein kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 24 publications
(20 reference statements)
2
110
0
1
Order By: Relevance
“…IFN antiviral activity was assayed biologically with vesicular stomatitis virus (VSV) in Madin-Darby bovine kidney cells (MDBK) cells as previously described (6,7). Briefly, supernatants of noninfected and ASFV-infected macrophages were collected, clarified by high-speed centrifugation (35,000 ϫ g, 1 h), acidified at pH 2, and neutralized with NaOH.…”
Section: Methodsmentioning
confidence: 99%
“…IFN antiviral activity was assayed biologically with vesicular stomatitis virus (VSV) in Madin-Darby bovine kidney cells (MDBK) cells as previously described (6,7). Briefly, supernatants of noninfected and ASFV-infected macrophages were collected, clarified by high-speed centrifugation (35,000 ϫ g, 1 h), acidified at pH 2, and neutralized with NaOH.…”
Section: Methodsmentioning
confidence: 99%
“…These results demonstrated that IP-10 plays a critical role in the IFN-induced protection against FMDV although presumably other ISGs may also be involved in inhibition of FMDV replication. As mentioned before, we have previously demonstrated in cell culture that PKR and the OAS/RNase L system control FMDV replication (6,28). It will be useful to examine the role of additional ISG products in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Disease was followed (A), and serum samples were collected for 7 days after challenge to assay for viremia (B). Serum of mice was tested for antiviral activity (C) and presence of IFN-␣ (D) at different time points (3,6, and 24 h) after VRP-GFP treatment before FMDV challenge. *, P Յ 0.05; **, P Յ 0.01; ***, P Յ 0.001. mice and PBS-treated IP-10 KO or WT mice (Fig.…”
Section: Ib-rs-2 Cells Do Not Respond To Vrp-gfp Infectionmentioning
confidence: 99%
See 2 more Smart Citations